Determining the factors that influenced customer's complaint: a case study at PERNEC Technologies Sdn. Bhd. / Nik Shila Azwin Nek Ahmad Kamal - Nek Ahmad Kamal, Nik Shila Azwin (Faculty of Business and Management, 2006)
It is important to understand and manage complaint behavior by the customer because it gives the organization an opportunity to retain its reputation and customer base by correcting the problem. If the organization does not respond effectively to the customer's complaint, then it is likely that the purchaser will become dissatisfied and voice his or her complaints to others. This type of behavior can harm the organization's reputation. This study determines the factors that influence customer's complaint. There appears factor’s that affects customer’s complaint which are regarding service content, delivery, communication, personnel, and response time. Specifically, the data was gathered from the questionnaire that had been distributed to the respondents. Data was obtained through personal and telephone interviews. Using the descriptive analysis and correlation coefficient analysis by the researcher, the study demonstrated that all the factors affect customer's complaint. It was revealed that: customer expect the timeframe to solve complaint will influence by the feedback given of customer service, customer expect the timeframe to solve complaint will influence by the time taken in term of delivery process, customer. Expect the timeframe to solve complaint will influence by the personnel's ability to answer customer questions, customer expect the timeframe in solve complaint will influence by the communication of Help desk person, and customer expect the timeframe in solve complaint will influence by the response time given, The main objective for all successful organizations is to minimize customer complaints. With the intention that firm should emphasize on the factors that affect customer's complaint in order to ensure that the customer will make less complaint. Firm should clear about the customers' requirements and understand their needs and the same time upgrades the service quality. Furthermore, firm is required to providing a speedy, accuracy" care attending the delivery process, and shortened the time taken to deliver the products and services. On the other hand, personnel must empower to deal with the any situation that involves with customers. Personnel also must increase their knowledge in term of products, technical knowledge, and communication skill. The firm is required to increase in communication skill like timely, clearly, concise, and informative. Moreover firm must make sure that response time given is clearly defined as per customers' requirements.